Reflections on International Criminal Justice: Past, Present and Future - Hans Corell (Washington University Global Studies Law Review, 2013)
The present symposium is focusing on Building the ICC: Challenges and Opportunities, the Early Jurisprudence of the Court, the United States and the ICC in the Decades Ahead, and on Imagining Future Directions of the Court. In agreement with the organizers, my address today will be on the topic Reflections on International Criminal Justice: Past, Present and Future. This will allow me to analyze the subject matter in a broader and more philosophical perspective. Also on this occasion, my address will be very personal.
Keywords: international criminal court; ICC; United Nations; international criminal justice; Whitney Harris; Nuremberg; human rights